Breakfast energy intake and dietary quality and trajectories of cardiometabolic risk factors in older adults - Karla-Alejandra Pérez-Vega; Camille Lassale; María-Dolores Zomeño; Olga Castañer; Jordi Salas-Salvadó; F. Javier Basterra-Gortari; Dolores Corella; Ramón Estruch; Emilio Ros; Francisco J. Tinahones; Gemma Blanchart; Mireia Malcampo; et al. (The Journal of Nutrition, Health and Aging)
Objectives: Not skipping breakfast is associated with a better overall diet quality and lower cardiometabolic risk. However, the impact of calorie intake and dietary quality of breakfast on cardiovascular health remains unexplored. We aimed to study the associations between breakfast energy intake and quality and time trajectories of cardiometabolic traits in high cardiovascular risk participants. Design: Prospective observational exploratory study with repeated measurements. Setting: Spanish older adults. Participants: 383 participants aged 55–75 with metabolic syndrome from PREDIMED-Plus, a clinical trial involving a weight-loss lifestyle intervention based on the Mediterranean diet. Measurements: Participants were followed for 36 months. Longitudinal averages of breakfast energy intake and quality were calculated. Three categories were defined for energy intake: 20−30% (reference), <20% (low), and >30% (high). Quality was estimated using the Meal Balance Index; categories were above (reference) or below the median score (low). Natural cubic spline mixed effects regressions described trajectories of cardiometabolic indicators (anthropometry, blood pressure, lipids, glucose, glycated hemoglobin, and kidney function) in breakfast groups. Inter-group differences in predicted values were estimated by linear regressions. Analyses were adjusted for age, sex, PREDIMED-Plus intervention group, education, smoking, physical activity, and total daily kilocalorie intake. Lipid profile analyses were further adjusted for baseline hypercholesterolemia, blood pressure analyses for baseline hypertension, and glucose/glycated hemoglobin analyses for baseline diabetes. Breakfast energy intake analyses were adjusted for breakfast quality, and vice versa. Results: At 36 months, compared to the reference, low- or high-energy breakfasts were associated with differences in body mass index (low: 0.61 kg/m² [95% confidence interval: 0.19; 1.02]; high: 1.18 kg/m² [0.71; 1.65]), waist circumference (low: 2.22 cm [0.96; 3.48]; high: 4.57 cm [3.13; 6.01]), triglycerides (low: 13.8 mg/dL [10.8; 16.8]; high: 28.1 cm [24.7; 31.6]), and HDL cholesterol (low: −2.13 mg/dL [−3.41; −0.85]; high: −4.56 mg/dL [−6.04; −3.09]). At 36 months, low-quality breakfast was associated with higher waist circumference (1.50 cm [0.53; 2.46]), and triglycerides (5.81 mg/dL [3.50; 8.12]) and less HDL cholesterol (−1.66 mg/dL [−2.63; −0.69]) and estimated glomerular filtration rate (−1.22 mL/min/1.73m2 [−2.02; −0.41]). Conclusions: Low- or high-energy and low-quality breakfasts were associated with higher adiposity and triglycerides, and lower HDL cholesterol in high-risk older adults. Low-quality breakfasts were also linked to poorer kidney function.